Sox11 Expression Promotes Regeneration of Some Retinal Ganglion Cell Types but Kills Others - Norsworthy, Michael (Neuron, 2017)
At least 30 types of retinal ganglion cell (RGC) send distinct messages through the optic nerve to the brain. Available strategies of promoting axon regeneration act on only some of these types. Here we tested the hypothesis that over-expressing developmentally important transcription factors in adult RGCs could reprogram them to a “youthful” growth-competent state and promote regeneration of other types. From a screen of transcription factors, we identified Sox11 as one that could induce substantial axon regeneration. Transcriptome profiling indicated that Sox11 activates genes involved in cytoskeletal remodeling and axon growth. Remarkably, alpha-RGCs, which preferentially regenerate following treatments such as PTEN deletion, were killed by Sox 11 overexpression. Thus, Sox 11 promotes regeneration of non-alpha RGCs, which are refractory to PTEN deletion-induced regeneration. We conclude that Sox11 can reprogram adult RGCs to a growth-competent state, suggesting that different growth-promoting interventions promote regeneration in distinct neuronal types.